Introduction - Aldunate, Nerea; Angulo, Rocío; Quezada-Scholz, Vanetza (Psykhe, 2022)
This special issue showcases a collection of nine articles that illustrate the rich diversity of experimental psychology research that is currently being carried out in Chile. This compilation of studies was born out of an initiative of the Basic Experimental Psychology Division of the Chilean Scientific Society of Psychology (Capítulo de Psicología Experimental Básica de la Sociedad Científica de Psicología de Chile, SCP), seeking to contribute not only to basic psychology but also to the development of evidence-based applied psychology, such as psychotherapeutic treatments. Some of these works result from international collaborations with researchers from countries such as EEUU, Spain, Netherlands, and Mexico, including authors who have been referents in their respective fields due to their significant contributions to scientific psychology. In addition, these nine studies illustrate how experimental psychology in Chile avails itself of a wide diversity of techniques and methods, ranging from behavioral observation to electrophysiological techniques and computational modeling, applying them to a wide variety of areas, including behavioral, cognitive, evolutionary, and social approaches.